AlN-AlN Layer Bonding and Its Thermal Characteristics. (24th April 2015) - Bao, S.; Lee, K. H.; Chong, G. Y.; Fitzgerald, E. A.; Tan, C. S.
Abstract : Homogeneous bonding was successfully demonstrated on 150 mm Si wafers by face-to-face direct dielectric bonding of clean and smooth aluminum nitride (AlN) layers. Characterization result from XPS confirms the layer composition and reveals that approximately 5 nm of the layer surface was partially oxidized during processing. After activation, substoichiometric nitrogen bound to aluminum, Al-O and Al-OH bonds were found at the thin film surface. The as-bonded wafer pairs are nearly void and particle free with a high bonding strength of 1527.8 ± 272.2 mJ/m 2, enabling them to withstand the subsequent process steps. In addition, experimental results have indicated that the AlN-AlN bonded wafers can achieve a 23 and 16% improvement respectively in terms of heat dissipation compared with those using SiO2 and Al2 O3 as the bonding layer. It is concluded that this AlN-AlN bonded wafer pairs can exhibit a better heat dissipation capability than other bonded counterparts.